Information technology (IT) with a human face : a collaborative research project to improve higher nutrition training in Southern Africa - Marais, Debbie (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.